Infectious diseases a clinical short course - Southwick, Frederick S. (McGraw-Hill, 2014)
A concise, thorough review of microorganisms and the diseases they cause No other resource makes clinical infectious diseases more manageable and easy to master than Infectious Diseases: A Clinical Short Course, Third Edition. This self-teaching tool is organized by system/region as opposed to pathogens -- simulating how common pathogens and disorders would be encountered in rounds or in practice. Unsurpassed for learning how to associate pathogens with their corresponding impact on actual patients Coverage of the entire field of infectious diseases in a concise presentation than can be read during a 30 day rotation Color photos show clinical manifestations of infectious diseases.